GREEN INHIBITORY EFFECT OF RED ONION PEEL EXTRACT ON THE CORROSION OF API 5L X-65 IN CO2 SATURATED ACIDIC MEDIUM - Maulana, Ikhsan
API 5L X65 carbon steel is often used as flowline and pipeline for flow of exploration natural gas for further processing. However in the oil industry, it is susceptible to corrosion attack on the surface of the outer and inner pipes. Corrosion attack on the inner surface of the pipe can be controlled using inhibitors. Inhibitors that are often used are chemical inhibitors that are toxic and not environmentally friendly. Therefore, green inhibitors are used that are environmentally friendly, economical, and can be adapted to work operations. In this study, the inhibitory efficiency of compound Quercetine will be tested from the peel onion extract (EKBM) with variation in the concentration from 10 to 50 ppm under condition NaCl 3% containing CO2 saturated acetic acid at room temperature by using Immersion Test for 120 hour, Electrochemical Impedance Spectroscopy (EIS), Potentiodinamic Tafel and surface analysis Scanning Electron Spectroscopy (SEM) Based on this observations, the corrosion rate increase with increasing acid concentration and the effect of CO2. Corrosion rate can be inhibited by EKBM which is a mixed inhibitor. On NaCl media containing 3360 ppm acetic acid saturated CO2 in room temperature, efficiency of EKBM based on tafel method and EIS is 38,06% and 63,93% %. And on Immersion Test, efficiency of EKBM in 24, 72, 120 hour reaches 85,72%, 53,89%, 60,72%. The mechanism of EKBM inhibition on metal surface is physical adsorption.